A LONGITUDINAL STUDY OF FACTORS AFFECTING MIGRANT SUBJECTIVE WELL-BEING: EMPIRICAL EVIDENCE FROM LATVIAN EMIGRANT SURVEYS - Koroļeva, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
People migrate for a variety of reasons, not only economic ones, but most expect to increase their quality of life and happiness by changing their place of residence. Most research on the integration of Eastern European migrants focuses primarily on their structural integration into the labour market, much less is known about the implications of migration on the general subjective well-being (SWB) of individuals. The terms ‘SWB’ and ‘happiness’ refer to people’s evaluations of their life which can be either cognitive or affective (e.g. Diener, 2009). From a theoretical perspective, migration decision-making can still be encompassed within a utility-maximising framework. Now, however, utility is captured by subjective judgements of satisfaction rather than monetary income. Quantitative data from two waves of a large-scale longitudinal survey of Latvian emigrants (2014 -2019 ) were used to identify the determinants of SWB and explore the impact of different factors (such as changes in family status, employment or health) on changes in life satisfaction over time.